Evaluation of the antimicrobial activity of essential oil and parts factions obtained from the species peltophorum dubium and combretum leprosum (Research, Society and Development, 2022)
The intensive use of antibiotics has caused a significant increase in the incidence of infections caused by multidrug-resistant bacteria and fungi in various parts of the world, which has motivated the isolation, characterization and evaluation of bioactivity of new drugs with potential antimicrobial action, or that are able to enhance the action of existing drugs. The objective of this work is to investigate the antimicrobial activities of the extracts and partition fractions obtained from the plants Peltophorum dubium and Combretum leprosum as well as to identify the phytochemicals involved in the already known investigated activities. All publications with data evaluating the antimicrobial activity of the essential oil and partition fractions obtained from the species Peltophorum dubium and Combretum leprosum were used, with emphasis on reproductive study in scientific publications. The data were collected using the scientific databases: LILACS, PUBMED, PERIODICOS CAPES, SCIENCE DIRECT, BVS, SCIELO, COCHRANE LIBRARY, HIGHWIRE PRESS, SCOPUS and ELSEVIER. A total of 15 articles on Peltophorum dubium and 23 articles on Combretum leprosum were selected from the scientific databases. The descriptors used were: Antimicrobial activity, Peltophorum dubium and Combretum leprosum, in English, Portuguese and Spanish. We obtained the articles described and discussed below in the form of topics related to the theme. Thus, isolating and characterizing the biological diversity of the Northeast, molecules with antimicrobial properties and or with modulating activity of resistance to industrialized drugs of current use, contributes not only to the exploitation of natural resources of this region, but also to justify and encourage policies of preservation of its ecosystems.